Detection of SARS-CoV-2 antibodies in a pet dogs and cats living in COVID-19-positive households in Iraq - Sajad Falih; Hazim Thwiny (Basrah Journal of Veterinary Research)
The goal of this study was to assess SARS-CoV-2 seroprevalence in pet dogs and cats during the coronavirus disease (COVID-19) pandemic in Iraq. Serum samples were collected from 180 animals, including 96 dogs and 84 cats. All animals included in this study were owned animals from a household with at least one COVID-19 patient. Serum samples from dogs and cats were screened for antibodies against SARS-CoV-2 using the commercial ELISA assay (ID Screen® SARS-CoV-2 Double Antigen Multi-species) according to the manufacturer’s instructions. The seroprevalences for SARS-CoV-2 was 7.3% for dogs and 8.3% for cats but this difference was not significant. Also, no significant different in seropositivity between age groups, sex and breeds of pet animals.  All positive animals did not show any clinical signs when contact with human SARS-CoV2 positive cases, suggesting that dogs and cats are likely asymptomatic carriers of SARS-CoV-2.